Immunosuppressive potential evaluation of synovial fluid mesenchymal stem cells grown on 3D scaffolds as an alternative source of MSCs for osteoarthritis cartilage studies - Paradiso, Francesca; Lenna, Stefania; Isbell, Reagan; Garcia Garza, Maria Fernanda; Williams, Michael; Varner, Catherine; Mcculloch, Patrick; Taraballi, Francesca (Frontiers in Biomaterials Science, 2022)
Osteoarthritis (OA) is a chronic degenerative joint disease, leading cause of disability in older adults and leads to pain, reduced mobility, and decreased quality of life. Mesenchymal stem cells (MSC) - based therapies are the precursor to all tissues within a joint and their potential in regeneration is complemented by a modulation of the local inflammatory response. The use of MSCS-based therapy for regenerative medicine, specifically OA, is challenged by the need to investigate the ideal MSC source, establish processing of harvesting and culture. Although bone marrow-derived mesenchymal stem cells (BM-MSCs) represent the gold standard in cell therapies for OA, synovial fluid-derived stem cells (SF-MSCs) can be a less invasive, promising alternative. Procedures to extract SFMSCs can be performed during arthrocentesis, arthroscopy or knee surgery with a minimally invasive act allowing personalized autologous therapies. SF-MSCs, isolated from human synovial fluid of patients suffering from advanced OA, retained stemness markers and inflammatory potential in 2D culture condition showing similar morphology and clonogenicity potential compared to BM-MSCs. To further boost their immunomodulatory properties, we coupled SF-MSCs with a biomimetic scaffold made of collagen and chondroitin sulfate (CL CS), previously reported as immune-tuning materials. The 3D culture further promoted immunosuppressive markers expression in SF-MSCs compared to 2D culture. Although ongoing clinical trials mainly used scaffold-free injection of MSCs, combination of mesenchymal cells and biomatrices could provide a useful tool to improve biological outcomes. A combination of SF-MSCs and 3D CL CS biomimetic scaffolds could represent a strong therapeutic effect as cell-based treatment for OA.